2012
DOI: 10.1371/journal.pone.0035646
|View full text |Cite
|
Sign up to set email alerts
|

MEKK1-MKK4-JNK-AP1 Pathway Negatively Regulates Rgs4 Expression in Colonic Smooth Muscle Cells

Abstract: Background Regulator of G-protein Signaling 4 (RGS4) plays an important role in regulating smooth muscle contraction, cardiac development, neural plasticity and psychiatric disorder. However, the underlying regulatory mechanisms remain elusive. Our recent studies have shown that upregulation of Rgs4 by interleukin (IL)-1β is mediated by the activation of NFκB signaling and modulated by extracellular signal-regulated kinases, p38 mitogen-activated protein kinase, and phosphoinositide-3 kinase. Here we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 108 publications
(180 reference statements)
1
15
0
Order By: Relevance
“…As shown in Fig. 1C, mutation of NFκB binding site inhibited while mutation of AP1 binding site enhanced the promoter activity of P4, consistent with our previous observation that NFκB signaling stimulates while AP1 signaling represses the transcription of RGS4[17, 19, 20]. Dual deletion of NFκB and AP1 sites induced a mixed effect on the P4 promoter activity.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As shown in Fig. 1C, mutation of NFκB binding site inhibited while mutation of AP1 binding site enhanced the promoter activity of P4, consistent with our previous observation that NFκB signaling stimulates while AP1 signaling represses the transcription of RGS4[17, 19, 20]. Dual deletion of NFκB and AP1 sites induced a mixed effect on the P4 promoter activity.…”
Section: Resultssupporting
confidence: 90%
“…The increase in RGS4 expression is responsible for IL-1β-induced inhibition of initial Ca 2+ -dependent smooth muscle contraction[16]. Up-regulation of RGS4 expression by IL-1β is mediated by the canonical IKK2/IκBα/NFκB signaling[17], enhanced by extracellular signal-regulated kinases (ERK1/2) and p38 mitogen-activated protein (MAP) kinase[18], and inhibited by phosphoinositide-3 kinase[18] and JNK pathway[19]. …”
Section: Introductionmentioning
confidence: 99%
“…They reported the activation of ERK1/2 and p38 MAPK enhances, and PI3K/Akt/GSK3β signaling reduces, the IL-1β-induced, NFκB-mediated RGS4 upregulation in rabbit colonic SMCs [60]. Furthermore, they also recently reported that JNK activation decreases RGS4 expression in the presence or absence of IL-1β stimulation [61]. Their results are opposite to those of the present study in terms of the direction of action of P38 MAPK and JNK, and differ in the presence or absence of ERK1/2 activation (we have not observed evident ERK1/2 activation by IL-1β).…”
Section: Discussionmentioning
confidence: 92%
“…This apparent discrepancy could be due to different durations of the phosphorylation state of JNK and c-Jun. In smooth muscle cells, the duration of JNK phosphorylation induced by interleukin-1b is shorter (30 min) than that of c-Jun (>2 h) (Zhang et al, 2012). As we analyzed 17 h after palmitate exposure, we may only have observed the long lasting c-Jun phosphorylation.…”
Section: Discussionmentioning
confidence: 94%
“…In smooth muscle cells, the duration of JNK phosphorylation induced by interleukin-1b is shorter (30 min) than that of c-Jun (>2 h) (Zhang et al, 2012). This apparent discrepancy could be due to different durations of the phosphorylation state of JNK and c-Jun.…”
Section: Discussionmentioning
confidence: 97%